Networks of Reciprocity: Precarity and Community Social Organisations in Rural Myanmar. Issue 4 (8th August 2019) - Griffiths, Michael
ABSTRACT: Growing precarity amongst rural households in Myanmar is characterised by increasingly debt-fuelled agriculture, decreasing sufficiency and sustainability of rural livelihoods and an absence of social safety nets. This constrains the capacity for viable livelihoods, as risk-averse coping strategies undermine long-term economic sustainability. In this context, informal support networks may be expected to decline or collapse. However, recent evidence demonstrates the widespread emergence of community-based social organisations in rural communities, formed along traditional principles of reciprocity. Analysis of large-scale rural household surveys demonstrates that such organisations are found in nearly 40% of communities in rural Myanmar. These organisations collect and redistribute funds to help with healthcare, education, funerals and other social needs. The presence of such organisations is linked to higher levels of household resilience, achieved through reducing the inequalities linked to gender, disability and poverty, and through providing enabling environments for effective income diversification. Communities with higher levels of migration are more likely to have community-based social organisations, possibly a result of economic and social remittances. In the absence of effective formalised social protection, these social organisations provide most of the social assistance in rural communities, representing new networks of reciprocity in the face of increasing precarity.